Diagnosis of the Relationship between Dust Storms over the Sahara Desert and Dust Deposit or Coloured Rain in the South Balkans - N. G. Prezerakos; A. G. Paliatsos; K. V. Koukouletsos (Advances in Meteorology)
The main objects of study in this paper are the synoptic scale atmospheric circulation systems associated with the rather frequent phenomenon of coloured rain and the very rare phenomenon of dust or sand deposits from a Saharan sandstorm triggered by a developing strong depression. Analysis of two such cases revealed that two days before the occurrence of the coloured rain or the dust deposits over Greece a sand storm appeared over the north-western Sahara desert. The flow in the entire troposphere is southerly/south-westerly with an upward vertical motion regime. If the atmospheric conditions over Greece favour rain then this rain contains a part of the dust cloud while the rest is drawn away downstream adopting a light yellow colour. In cases where the atmospheric circulation on the route of the dust cloud trajectories is not intensively anticyclonic dust deposits can occur on the surface long far from the region of the dust origin. Such was the case on 4th April, 1988, when significant synoptic-scale subsidence occurred over Italy and towards Greece. The upper air data, in the form of synoptic maps, illustrate in detail the synoptic-scale atmospheric circulations associated with the emission-transport-deposition and confirm the transportation of dust particles.